2022
DOI: 10.1002/fsn3.2885
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and safety features assessment of Weissella spp. from environmental sources

Abstract: Weissella strains have been reported to be useful in biotechnological and probiotic determinations, and some of them are considered opportunistic pathogens. Given the widespread interest about antimicrobial susceptibilities, transmission of resistances, and virulence factors, there is little research available on such topics for Weissella. The aim of this study was to assess the safety aspects and antimicrobial potential of 54 Weissella spp. strains from different environmental sources. Antibiotic susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 111 publications
4
7
0
Order By: Relevance
“…With the exception of P. beninensis LMG 25373 T and W. diestrammenae DSM 27940 T , all the analyzed type strains were classified as resistant to chloramphenicol. Similar to our findings, high MIC values for chloramphenicol (even 16 and 32 mg/L) were also reported for some Weissella confusa strains in previous studies ( 63 , 65 ). Considering this, the presence of specific chloramphenicol resistance genes was suggested in Weissella spp.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…With the exception of P. beninensis LMG 25373 T and W. diestrammenae DSM 27940 T , all the analyzed type strains were classified as resistant to chloramphenicol. Similar to our findings, high MIC values for chloramphenicol (even 16 and 32 mg/L) were also reported for some Weissella confusa strains in previous studies ( 63 , 65 ). Considering this, the presence of specific chloramphenicol resistance genes was suggested in Weissella spp.…”
Section: Discussionsupporting
confidence: 92%
“…( 65 ). Nonetheless, the presence of the cat gene coding for a chloramphenicol acetyltransferase, which is the most common chloramphenicol resistance gene in LAB ( 64 ), was not detected in chloramphenicol-resistant Weissella strains ( 63 ), in line with our results. In light of this, and as proposed for the related genus Leuconostoc ( 64 ), the possibility of an intrinsic resistance to chloramphenicol in Weissella spp.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although Weissella are intrinsically resistant to vancomycin (Ahmed et al, 2022), the resistance is most likely not easily transferred to pathogenic microbes. A very recent study by Fhoula et al (2022) showed that although W. paramesenteroides strain could receive antibiotic resistance genes from Bacillus strains at very low frequency of 10 −9 transconjugant per recipient, Weissella strains were not able to transfer their antibiotic resistance genes to Enterococcus strains. Biogenic amines accumulated by the microorganisms in fermented foods can cause adverse effects to human (Alvarez and Moreno-Arribas, 2014).…”
Section: Discussionmentioning
confidence: 99%